Analysis Inequality Income in Indonesia 2020 - Muhtar Muhtar; Diah Lutfi W (Journal of International Conference Proceedings, 2021)
Income inequality is a reality that exists in the midst of the world community, both developing and developed countries. Income inequality Â (Gini Index) can cause social turmoil in society such as crime rates etc. The purpose of this study is to analyze income in Indonesia. The research method used is quantitative, with multiple linear regression analysis tools. The data used is secondary data obtained from the Central Statistics Agency in 2020. Quantitative analysis was conducted to determine the factors that influence income inequality in the 2020 period, namely the Human Development Index (HDI) and the Unemployment Rate. parsia, the human development index has a positive and significant effect on income inequality, while the unemployment rate has no significant effect on Gini Index. The implications are expected to be regulations that can improve education, health and per capita income.